Effect of humidity and temperature on proton conduction in phosphonated copolymers. (September 2019) - Kumar, Avneesh; Pisula, Wojciech; Müllen, Klaus
Graphical abstract: Phosphonated block copolymers based on PVBPA and PPO are investigated for their performance against the sulfonated Nafion. The block copolymers demonstrate a competent efficiency. and can be used as membrane materials in fuel cells excluding rather expensive sulfonated ionomers. Abstract: Phosphonated block copolymers based on poly(vinylbenzyl phosphonic acid) are examined under varied humidity and temperatures for their proton conducting properties. The copolymers have rod-like poly(phenylene oxide) block that induces ordered domains. The ordered and crystalline domains are associated with higher proton conductivity. The highest conductivity approaching 10 −2 S/cm was determined under ambient conditions for the copolymer with a rather shorter PPO block. Scanning electron microscopy images of the copolymer reveal interconnected ionic domains that are related directly with the higher conduction in phosphonated block copolymer. A comparative study with sulfonated Nafion suggests that phosphonated polymers too can be used in fuel cell operating at a high temperature range.